Intervención del terapista respiratorio en paciente femenino de 63 años con insuficiencia respiratoria por covid -19. - Allan Guano, Ricardo Alexander (2022)
This clinical case is about oxygen therapy in a 63-year-old female patient with respiratory failure due to COVID -19. The objective of the research will be to identify the clinical manifestations of acute respiratory failure in patients over 60 years of age. The results obtained during the investigation were: acute respiratory insufficiency is a pathology that produces the inability to breathe properly, which is aggravated in people over 60 years of age. The conclusion of the clinical case is that the disease, no matter how great it may be, will always have consequences and despite everything, it was possible to maintain the patient with the appropriate techniques.